The effect of feeding frequency on the growth, reproduction performance, body composition and digestive enzyme activity of Penaeus monodon broodstock - Jiang, Song; Zhou, Fa‐lin; Yang, Qi‐bin; Huang, Jian‐hua; Yang, Li‐shi; Jiang, Shi‐gui (Aquaculture research, 2020)
In this study, the effect of different feeding frequency (TA: twice/day, TB: 3 times/day, TC: 4 times/day) on the feeding, growth, reproductive performance, body composition and digestive enzyme activity of hepatopancreas of Penaeus monodon broodstock was compared. The living Nereis succinea were used to feed the P. monodon broodstock for 8 weeks to explore the most appropriate feeding frequency during the breeding period. The results showed that the daily feeding amount of P. monodon broodstock increased with the increase of feeding frequency, and the daily feeding amount of TA group was significantly lower than that of TB and TC group (p < .05), but the difference between TB group and TC group was not significant (p > .05). There was no significant difference on the spawning amount, the number of the nauplius I individuals, the hatchability of nauplius, the number of the zoaea larva I individuals, the metamorphosis rate, the gonadal index and the first spawning time when Penaeus monodon broodstock was fed in different frequency (p > .05). The relative fecundity of TA group was significantly lower than that of TB and TC group (p < .05), and the difference between TB and TC group was not significant (p > .05). The spawning interval of TA group was significantly higher than that of TB and TC group (p < .05), and the difference between TB and TC group was not significant (p > .05). The contents of moisture, crude protein, crude fat and ash of the P. monodon broodstock body were not affected by the increase of the feeding frequency (p > .05). The activities of trypsin and lipase in TA group were significantly lower than those in TB and TC group (p < .05), while the activities of pepsin and amylase in different experimental groups were not significantly different (p > .05). According to the results of this study and the actual situation of production, it is suggested that the suitable feeding frequency of nutrition enhancement period during the reproduction of P. monodon broodstock is 3 times/day in the condition of satiation.